2017
DOI: 10.3847/1538-4357/835/1/101
|View full text |Cite
|
Sign up to set email alerts
|

Globular Cluster Systems in Brightest Cluster Galaxies. Iii. Beyond Bimodality

Abstract: We present new deep photometry of the rich globular cluster (GC) systems around the Brightest Cluster Galaxies UGC 9799 (Abell 2052) and UGC 10143 (Abell 2147), obtained with the Hubble Space Telescope (HST) ACS and WFC3 cameras. For comparison, we also present new reductions of similar HST/ACS data for the Coma supergiants NGC 4874 and 4889. All four of these galaxies have huge cluster populations (to the radial limits of our data, comprising from 12,000 to 23,000 clusters per galaxy). The metallicity distrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 157 publications
(305 reference statements)
2
82
0
7
Order By: Relevance
“…where M g is the cold gas mass in the galaxy and the normalization of equation (2) is motivated by the cosmological hydrodynamic simulations of Kravtsov & Gnedin (2005). The values of p 2 and p 3 are taken to be free parameters 1 , whose values are constrained using a wide array of observational data on GC system metallicities and masses (Harris 1996;Côté et al 2006;Peng et al 2006;Harris et al 2014Harris et al , 2016Harris et al , 2017a. The cold gas fraction is parameterized as a function of the stellar mass M and redshift z as:…”
Section: Summary Of Cluster Formation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where M g is the cold gas mass in the galaxy and the normalization of equation (2) is motivated by the cosmological hydrodynamic simulations of Kravtsov & Gnedin (2005). The values of p 2 and p 3 are taken to be free parameters 1 , whose values are constrained using a wide array of observational data on GC system metallicities and masses (Harris 1996;Côté et al 2006;Peng et al 2006;Harris et al 2014Harris et al , 2016Harris et al , 2017a. The cold gas fraction is parameterized as a function of the stellar mass M and redshift z as:…”
Section: Summary Of Cluster Formation Modelmentioning
confidence: 99%
“…The mean and dispersion of GC system MDFs have also been found to scale with the mass of the host galaxy over a large range in galaxy mass (Peng et al 2006). Qualitatively, many galaxies have clearly multi-modal MDF (e.g., Gebhardt & Kissler-Patig 1999;Peng et al 2006;Brodie & Strader 2006;Brodie et al 2012), but the most massive galaxies typically show broad, single-peaked distributions (Harris et al , 2016(Harris et al , 2017a.…”
Section: Introductionmentioning
confidence: 99%
“…All of these galaxies are listed in HR17. To this sample we include four massive, central dominant ETGs studied by Harris et al (2017b). Relevant properties of the sample galaxies and references are given in Table 1.…”
Section: The Samplementioning
confidence: 99%
“…For example, [29] has shown that the (g − z ) color distributions of the GCs of several galaxies in Virgo and Fornax seem to display a common and synchronized multi-population pattern. Furthermore, [16] proposed that in some massive galaxies, the metallicity distribution might be thought of as the result of a rapid sequence of individual GC formation events leading to an apparent "continuous" metallicity distribution. In the particular case of NGC 1395, though preliminary, our results seem to fit in these pictures.…”
Section: Discussionmentioning
confidence: 99%
“…In the [12] scenario, the morphology of the horizontal branch (HB) produces a "wavy" pattern in the C-M relation in such a way that it is possible to obtain a bimodal color distribution from a unimodal metallicity distribution. Despite several empirical C-M calibrations have been published in the last decade, there is still a lot of controversy about the existence of the alleged "wavy" pattern, i.e., how strong it is, and how much it influences our interpretation of multiple GC populations based on broad-band colors ( [13][14][15][16]). …”
Section: Introductionmentioning
confidence: 99%